(untitled) (Research, Society and Development, 2023)
Objectives: To identify risk management tools for the safety of patients with suicidal behavior, used in hospital emergencies. Methodology: Integrative literature review, from 2017 to 2021, in order to answer the research’s guiding question: What are the management tools used in risk management and patient safety in suicidal behavior in the hospital environment? The PICO search strategy was used and the selection of studies was carried out independently by two reviewers, who used Scopus, Web of Science and Pubmed databases as search sources. Results: 863 articles were identified, of which 8 were selected. It was observed in the studies that the management tools were: Service protocols; Failure Mode and Effects Analysis in Healthcare (HFMEA); Checklist and the Safety Huddle. Conclusions: Risk management tools for the safety of patients with suicidal behavior used in hospital emergencies show positive results in relation to suicide prevention in these environments and that contribute to quality and safe care, but lack more scientific evidence.